Jaundice as a presenting symptom of large B-cell lymphoma. Issue 5 (15th September 2022) - Bejcek, Alexis; Ancha, Anupama; Lewis, Megan; Khan, Shamyal; Ramirez, Jonathan
Abstract: Jaundice can be caused by a wide variety of disorders in adults including pancreatic malignancy. Most pancreatic malignancies are primary in origin. However, other malignancies, including lymphomas, may present as secondary pancreatic masses, with a variety of clinicopathologic features and outcomes for patients. This study describes a patient with previous tobacco use who was diagnosed with a pancreatic mass and found to have diffuse large B-cell lymphoma.